Early subcellular Ca2+ remodelling and increased propensity for Ca2+ alternans in left atrial myocytes from hypertensive rats. (17th February 2015) - Pluteanu, Florentina; Heß, Johannes; Plackic, Jelena; Nikonova, Yulia; Preisenberger, Judit; Bukowska, Alicja; Schotten, Ulrich; Rinne, Andreas; Kienitz, Marie-Cecile; Schäfer, Martin K.-H.; Weihe, Eberhard; Goette, Andreas; et al.
Abstract: Aims: Hypertension is a major risk factor for atrial fibrillation. We hypothesized that arterial hypertension would alter atrial myocyte calcium (Ca 2+ ) handling and that these alterations would serve to trigger atrial tachyarrhythmias. Methods and results: Left atria or left atrial (LA) myocytes were isolated from spontaneously hypertensive rats (SHR) or normotensive Wistar-Kyoto (WKY) controls. Early after the onset of hypertension, at 3 months of age, there were no differences in Ca 2+ transients (CaTs) or expression and phosphorylation of Ca 2+ handling proteins between SHR and WKY. At 7 months of age, when left ventricular (LV) hypertrophy had progressed and markers of fibrosis were increased in left atrium, CaTs (at 1 Hz stimulation) were still unchanged. Subcellular alterations in Ca 2+ handling were observed, however, in SHR atrial myocytes including (i) reduced expression of the α1C subunit of and reduced Ca 2+ influx through L-type Ca 2+ channels, (ii) reduced expression of ryanodine receptors with increased phosphorylation at Ser2808, (iii) decreased activity of the Na + /Ca 2+ exchanger (at unaltered intracellular Na + concentration), and (iv) increased SR Ca 2+ load with reduced fractional release. These changes were associated with an increased propensity of SHR atrial myocytes to develop frequency-dependent, arrhythmogenic Ca 2+ alternans. Conclusions: In SHR, hypertension induces early subcellular LA myocyte Ca 2+ remodelling during compensated LV hypertrophy. In basal conditions, atrial myocyte CaTs are not changed. At increased stimulation frequency, however, SHR atrial myocytes become more prone to arrhythmogenic Ca 2+ alternans, suggesting a link between hypertension, atrial Ca 2+ homeostasis, and development of atrial tachyarrhythmias.